2013
DOI: 10.2135/cropsci2012.06.0340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increasing Rumen‐Undegradable Protein Supplementation Levels on Early Weaned Calves Grazing Stargrass

Abstract: RESEARCH E arly weaning of beef calves is an effective management practice to increase the likelihood of rebreeding of first-calf beef heifers in the southeast United States (Arthington and Kalmbacher, 2003). Arthington and Kalmbacher (2003) observed that performance of early weaned calves (90 d of age) grazing annual ryegrass (Lolium multiflorum Lam.) and supplemented with 1% body weight (BW) concentrate was similar to the performance of calves that were not early weaned and remained on bahiagrass (Paspalum n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Inyang et al (2010a) observed that HA of less than 1.4 kg DM kg -1 LW decreased ADG of heifers grazing bahiagrass and brachiariagrass pastures. Vendramini et al (2013) observed that 10 g kg -1 of body weight of concentrate supplementation was approximately 33% of the total DM intake of early weaned calves receiving stargrass. Vendramini et al (2007) observed that early weaned calves grazing Tifton 85 bermudagrass increased ADG from 0.4 to 0.5 kg d -1 with increasing levels of supplementation from 0 to 10 g kg -1 concentrate supplementation at similar HA (»1.0 kg DM kg -1 LW) between treatments.…”
Section: Animal Responsesmentioning
confidence: 96%
See 1 more Smart Citation
“…Inyang et al (2010a) observed that HA of less than 1.4 kg DM kg -1 LW decreased ADG of heifers grazing bahiagrass and brachiariagrass pastures. Vendramini et al (2013) observed that 10 g kg -1 of body weight of concentrate supplementation was approximately 33% of the total DM intake of early weaned calves receiving stargrass. Vendramini et al (2007) observed that early weaned calves grazing Tifton 85 bermudagrass increased ADG from 0.4 to 0.5 kg d -1 with increasing levels of supplementation from 0 to 10 g kg -1 concentrate supplementation at similar HA (»1.0 kg DM kg -1 LW) between treatments.…”
Section: Animal Responsesmentioning
confidence: 96%
“…Vendramini et al (2007) observed that early weaned calves grazing Tifton 85 bermudagrass increased ADG from 0.4 to 0.5 kg d -1 with increasing levels of supplementation from 0 to 10 g kg -1 concentrate supplementation at similar HA (»1.0 kg DM kg -1 LW) between treatments. Vendramini et al (2013) observed that 10 g kg -1 of body weight of concentrate supplementation was approximately 33% of the total DM intake of early weaned calves receiving stargrass. However, Vendramini and Arthington (2008) reported that there was a decrease in ADG of early weaned calves grazing stargrass pastures when HA decreased from 1.0 to 0.7 kg DM kg -1 LW.…”
Section: Animal Responsesmentioning
confidence: 96%
“…Thus, PS was effective to optimize the environment in the rumen, and consequently improving both protein nutrition and energy nutrition. This supplement has been shown to be effective after weaning by Vendramini et al (2013) and Euclides et al (2014).…”
Section: Supplement Effectsmentioning
confidence: 99%